Experimental Study of Command and Reciprocal Teaching Styles on Improving Upper Service Learning Outcomes in Volleyball Games for Physical Education, Health and Recreation Students, Cenderawasih University - Marsuki (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study was conducted to determine the effect of reciprocal teaching style and command teaching style on upper serve ability in volleyball. The method used is an experimental method using the Pretest Posttest Control Group Design; in this design, a sample is obtained based on the size of the population, then an initial test or pre-test is held. The population in this study was students of the Teaching and Education Faculty of Penjaskesrek, Cenderawasih University. Based on the results of the calculations, it is stated that the command teaching method is more influential than the reciprocal teaching method on the upper serve ability in volleyball. This is based on the value of tcount = 7.42 > ttable = 2.101, with a level of α = 0.05. As a recommendation for coaches and coaches, in improving the ability to serve in volleyball games, they can apply the command teaching method.